Community knowledge, awareness and participation in controlling forest fire in Klias Peninsula Peat Swamp Forest, Sabah - Najjah Salfinas Mat Fisal (2023)
In Malaysia, human negligence and agricultural activity are the main causes of forest fires. Peat swamp forests, secondary forests, forest plantations, and loggedover forests are among the Malaysian forest types where fires commonly occur. In agricultural and plantation areas, slash-and-burn practices are consistently used as the most economical method for land conversion. The Klias Peninsula's peat swamp forest is still in danger of further degrading due to attempts to convert land and sporadic fires. The Sabah government is aware that protecting forests by themselves will not be sufficient to maintain the integrity of the peatlands region. As a result, they understand the need to increase community awareness of the causes and effects of human activity and their participation in maintaining the integrity of these ecosystems. The community's lifestyle decisions predict peatland forest fire, which shows a lack of understanding of the importance of peat swamp forests. This study was conducted in Klias Peninsula, Beaufort, Sabah, to determine and evaluate the level of community awareness and their participation in forest fire prevention. A random sample size of 30% of the population was selected based on the total number of villages in the three forest reserves used for this study: Klias Forest Reserves, Binsuluk Forest Reserves, and Padas Damit Forest Reserves. Four hundred respondents received the questionnaire through the village head or JKKK Village, but only 227 returned it in full. Non-probability and household-convenient samples were used in this study's sampling procedures. The community's level of awareness, perception, and preference participation towards community development projects is determined using descriptive analysis. These were highly validated by scientific analysis such as Kruskal-Wallis analysis, post-hoc testing using Dunn's test with Bonferroni correction, and Spearman's correlation. According to the study's findings, the local population is generally aware of and knowledgeable about preventing forest fires in peat swamp forests. It results from one of the Authority's previous awareness campaign's failure. The campaign's failure can be attributed to the fact that the same people attend the bulk of awareness events because communities' access to knowledge and information is constrained and manipulated by someone irresponsible. Despite having equal attitudes toward forest fire prevention and firefighting techniques, it was shown that men have more knowledge about preventing forest fires than women do. The study also discovered that the majority of the communities in Klias Peninsula believed that modern mechanical forces, followed by natural disasters and human irresponsibility were the causes of forest fires in their nearby forest reserves. Yet, it is reasonable to conclude that irresponsibility and human activity are the primary causes of forest fires in the Klias Peninsula. By collaborating with the relevant authority to prevent and put out forest fires, the community, on the other hand, responds positively. The two community development programmes chosen by the locals from the four offered in this study were the Educational & Awareness Community Development Program and the Agricultural Community Development Program. The community should be more understanding and aggressively promote its status as a burn-free community while preserving the forest reserves' resources for future generations.